2018
DOI: 10.21580/wjc.v2i1.2669
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktivitas Antimikroba Daun Sirsak (Annona muricata L.) Terhadap Bacillus subtillis dan Eschericia coli

Abstract: Tujuan penelitian ini adalah untuk mengetahui aktivitas antimkroba dari ekstrak daun sirsak terhadap <em>Bacillus subtilis</em> dan <em>Esherichia coli. </em>Ekstrak daun sirsak diperoleh dengan cara ekstraksi menggunakan metode Soxhletasi dengan pelarut n-heksana dan metanol. Subjek dalam penelitian ini adalah ekstrak daun sirsak. Ekstraksi dilakukan dengan metode soxletasi dengan 8 sirkulasi. Identifikasi senyawa antimikroba menggunakan metode cakram/ <em>paper disc</… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, it was found that the highest inhibitory zone diameter was 9 mm in AKR3 against the growth of S. epidermidis and AKRX against the growth of C. albicans which were classified as moderate activity. In previous studies, Fibonacci and Hulyadi (2018) have tested antimicrobial activity on Bacillus subtilis and Eschericia coli using soursop leaf extract with successive inhibition zone results of 12 mm and 10 mm [16]. Silitonga (2019) also researched the effectiveness of soursop leaf extract in ethanol and ethyl acetate solvents.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it was found that the highest inhibitory zone diameter was 9 mm in AKR3 against the growth of S. epidermidis and AKRX against the growth of C. albicans which were classified as moderate activity. In previous studies, Fibonacci and Hulyadi (2018) have tested antimicrobial activity on Bacillus subtilis and Eschericia coli using soursop leaf extract with successive inhibition zone results of 12 mm and 10 mm [16]. Silitonga (2019) also researched the effectiveness of soursop leaf extract in ethanol and ethyl acetate solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Water can dissolve some polar compounds contained in A.bilimbi fruit and C.odorata flowers to work to inhibit the test bacteria. Water is a universal solvent that can dissolve secondary compounds of flavonoids, phenols, anthraquinones, alkaloids, and tannins (Fibonacci & Hulyadi, 2018). Secondary compounds can destroy bacterial cell walls and inhibit bacterial growth (Abuga et al, 2020;Prastiyanto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%